Acute Toxicity and Antipyretic Test of Ethanol Extract of Sterculia Quadrifida. R. Br. Leaves as Traditional Medicine - Fernandez, Stefany S.A; Mbunga, Dominus; Amaral, Acacio Cardoso; Lau, Lidia; Feoh, Putriasa G (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Sterculia quadrifida (SQ) is a plant which is also known as